Pengaruh Kompensasi, Kepuasan Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan pada Leasing Adira Finance Syariah - Sari, Lutfiana Novita; Tho'in, Muhammad (Nur Science Institute, 2023)
This study aims to determine the effect of compensation, job satisfaction and work motivation on employee performance at the Sukoharjo Adira Finance Sharia Leasing Branch Office. The research method uses a quantitative descriptive approach. The population used was all employees at Adira Finance Sharia Leasing, totaling 52 people, all of whom were sampled. The data analysis method used is descriptive statistical test, research instrument test, classic assumption test, and hypothesis testing (multiple linear regression, t test, F test, and coefficient of determination test (R2).The results showed that compensation affects employee performance; Job satisfaction affects employee performance, and work motivation influences employee performance at Adira Finance Sharia Leasing of Sukoharjo Branch Office. The three variables indicate that work motivation most dominantly influences employee performance at the Adira Finance Sharia Leasing of Sukoharjo Branch Office, a tcount value of 7.604 is obtained > from ttable of 0.543.